Pico hydro propeller turbine prototype experimental study for very low head applications - Subekti, Ridwan Arief; Mohd-Zawawi, Fazila; Ismail, Kamarulafizam; Ishak, Iskandar Shah; Sudibyo, Henny; Susatyo, Anjar; Pikra, Ghalya; Radiansah, Yadi; Aziz, Amiral; Fudholi, Ahmad (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
There is a lot of untapped potential for low-head and very low-head (VLH) hydroelectric power in Indonesia. The challenge in developing VLH is that the locations are very difficult to access by vehicle. One example is in the interior of South Kalimantan Province, where it takes more than 12 hours to reach the location on foot. This paper discusses an experimental study of a pico hydro propeller turbine prototype for VLH applications which is suitable for use in remote areas of Indonesia. Its design is simple and lightweight, and it is made from PVC. The turbine's specifications include a power output of 250 W with a net head of 1.53 m. The turbine was designed with four different runner models, including variations in the number of blades and their geometric shapes. The runner models are type 1 and 2 with five and four blades, respectively, and type 3 (in a shallow configuration) and type 4 (in a steep configuration) with 3 blades. The generator used was a DC, 36 V, with a maximum power of 500 W, 2,500 rpm, and 1 phase. An AC lamp was used as the generator load, so an inverter from DC to AC was used in this test. The propeller turbine was tested in the laboratory. The experiments were conducted at various flow rates by adjusting the rotational speed of the supply pump and the electrical load using incandescent lamps. The test results are presented as graphs showing the relationship between flow rate and rotational speed, hydraulic and electrical power, and efficiency. The experimental results indicate that the turbine with a type 3 runner model featuring three blades in a gentle slope configuration has the highest efficiency, approximately 72.5 %.